The Construction of Morality Educational Concept (Analysis of Thinking Hamka) - muhammad Bahrudin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Abstract: This research is motivated by the problems of moral degradation of teenagers and the role of the model in Indonesian society today. Therefore, it is needed to examine the characters who become role models and thoughts about manners to produce the seeds of the successor of the noble nation of noble character. This research uses qualitative approach. This means that the approach by thinking the opinions of experts or phenomena that exist in people's lives. This type of research using research type library research that collects data or scientific papers that aims with the object of research or collecting data that is literary. In collecting data, the author uses documentation techniques. As for the technique of data analysis using content analysis, namely data processing by separate sorting related to the discussion of some ideas or thoughts of educational leaders who later described, discussed and criticized. The results of this study conclude that the concept of moral character education perspective based on Al-Qur'an and Sunnah Rasulullah SAW and Reason. The goal of human rights perspective education is to reach the i'tidal (soul balance) achieved by developing four factors, namely syaja'ah, 'iffah, wisdom, and' is. A prominent method of morality education of HAMKA is the method of virtue, exemplary method, live in method, and method of habituation. The most appealing evaluation for character education of human rights perspective is muhasabah (self-evaluation).Keywords: Concept of Education, Character, Hamka